EGF-Receptor Phosphorylation and Downstream Signaling are Activated by Benzo[a]pyrene 3,6-quinone and Benzo[a]pyrene 1,6-quinone in Human Mammary Epithelial Cells - Rodríguez-Fragoso, Lourdes (2009)
Benzo[a]pyrene (BaP) is activated by xenobiotic-metabolizing enzymes to highly mutagenic and carcinogenic metabolites. Previous studies in this laboratory have shown that benzo(a)pyrene quinones (BPQs), 1,6-BPQ and 3,6-BPQ, are able to induce epidermal growth factor receptor (EGFR) cell signaling through the production of reactive oxygen species. Recently, we have reported that BPQs have the potential to induce the expression of genes involved in numerous pathways associated with cell proliferation and survival in human mammary epithelial cells. In the present study we demonstrated that BPQs not only induced EGFR tyrosine autophosphorylation, but also induced EGFR-dependent tyrosine phosphorylation of phospholipase C-γ1 and several signal transducers and activators of transcription (STATs). The effects of BPQs were evaluated in a model of EGF withdrawal in MCF10-A cells. We found that BPQs (1 μM), induced EGFR tyrosine phosphorylation at positions Y845, Y992, Y1068, and Y1086. PLC-γ1 phosphorylation correlated with the phosphorylation of tyrosine-Y992, a proposed docking site for PLC-γ1 on the EGFR. Additionally, we found that BPQs induced the activation of STAT-1, STAT-3, STAT-5a and STAT-5b. STAT5 was shown to translocate to the nucleus following 3,6-BPQ and 1,6-BPQ exposures. Although the pattern of phosphorylation at EGFR, PLC-γ1 and STATs were quite similar to those induced by EGF, an important difference between BPQ-mediated signaling of the EGFR was observed. Signaling produced by EGF ligand produced a rapid disappearance of EGFR from the cell surface, whereas BPQ signaling maintained EGFR receptors on the cell membrane. Thus, the results of these studies show that 1,6-BPQ and 3,6-BPQ can produce early events as evidenced by EGFR expression, and a prolonged transactivation of EGFR leading to downstream cell signaling pathways.